Vitamin D and Its Role in Oral Diseases Development. Scoping Review - Ekaterina Diachkova; Daria Trifonova; Elena Morozova; Gyuzel Runova; Igor Ashurko; Maria Ibadulaeva; Valentin Fadeev; Svetlana Tarasenko (MDPI AG, 2021)
Vitamin D is a fat-soluble secosteroid that plays a significant role in the whole body, including the maxillofacial region. The discovery of its receptors in many cells and organs made it possible to reveal the participation of vitamin D not only in the regulation of calcium phosphate metabolism, but also in immune processes, in providing anti-inflammatory and antimicrobial effects, slowing down cell proliferation and stimulating differentiation. In this literature review, we demonstrate the association between low vitamin D levels and the development of recurrent aphthous stomatitis, the course and response to treatment of squamous cell carcinoma of the oral cavity, the severity of periodontal diseases, and the processes of osseointegration and bone remodeling during dental implantation and guided tissue regeneration. The aim of our article was to demonstate a possible connection between vitamin D level and the oral diseases that can be presented at an oral surgery appointment, which will help clinicians to reduce the risk of early dental implant failure, ensure favorable outcomes of augmentative operations, as well as decrease the destructive effects of severe periodontitis and other conditions throug knowledge and timely lab tests and endocrinologist prescriptions.